2010
DOI: 10.1186/1471-2091-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the acyl-CoA synthetase ACSL6 isoforms: role of the fatty acid Gate-domains

Abstract: BackgroundActivation of fatty acids by acyl-CoA synthetase enzymes is required for de novo lipid synthesis, fatty acid catabolism, and remodeling of biological membranes. Human long-chain acyl-CoA synthetase member 6, ASCL6, is a form present in the plasma membrane of cells. Splicing events affecting the amino-terminus and alternative motifs near the ATP-binding site generate different isoforms of ACSL6.ResultsIsoforms with different fatty acid Gate-domain motifs have different activity and the form lacking th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
0
41
0
2
Order By: Relevance
“…We also found an apparently fixed and damaging variant of a PLTP orthologue, the protein product of which is involved in the synthesis and catabolism of high-density lipo-protein (38) and may affect the availability of triglycerides and weight gain during hyperphagia in PBs. In addition, we found fixed variants in two putative orthologues involved in longchain fatty acid synthesis and catabolism: CPT1B and ACSL6 (39,40). The fixed variants in these genes may be related to the fatty acid profile of PBs.…”
Section: Adaptation Of Pbs To Arctic Environment: Potential Signals Omentioning
confidence: 89%
“…We also found an apparently fixed and damaging variant of a PLTP orthologue, the protein product of which is involved in the synthesis and catabolism of high-density lipo-protein (38) and may affect the availability of triglycerides and weight gain during hyperphagia in PBs. In addition, we found fixed variants in two putative orthologues involved in longchain fatty acid synthesis and catabolism: CPT1B and ACSL6 (39,40). The fixed variants in these genes may be related to the fatty acid profile of PBs.…”
Section: Adaptation Of Pbs To Arctic Environment: Potential Signals Omentioning
confidence: 89%
“…Genes related to lipogenesis were significantly decreased in mice fed the HS diet, including those involved in fatty acid and lipid biosynthesis and transport (Scd2, Fabp5, Thrsp and Hmgcr) 2023 , lipid endocytosis (Ldlr) 24 , and lipid esterification (Dgat2, Mogat2 and Plin2) 2527 . Acsl6 is a negative regulator of lipid metabolism 28 . Conversely, genes related to lipolysis and fatty acid decomposition (specifically, Fabp3, Cpt1b, and Acot3) 2931 , or carbohydrate utilization (Pck1 and Pdk4) 32, 33 were significantly up-regulated by the HS diet.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by studies in rat brain, where it was observed to be involved in the incorporation of unsaturated fatty acids into phospholipids (Soupene et al . ; Chen et al . ).…”
Section: Discussionmentioning
confidence: 99%